The physicochemical characteristics of whey dangke fermentation powder at various levels of carrageenan and drying time - Wahniyathi Hatta; Farida Nur Yuliati; Endah Murpi Ningrum (Faculty of Animal Science, Universitas Brawijaya, 2019)
Whey dangke fermentation producing lactic acid as a food additive can overcome environmental pollution caused by whey dangke; however, its high water content causes a short shelflife product and makes distribution difficult. Drying fermented products requires additional ingredients to overcome stickiness issue in the dryer. This research aimed to examine the use of carrageenan as drying aids at 4, 6, 8, and 10% levels and drying time of 23, 24, and 25 hours in the production of fermented whey powder in drying oven. The quality parameters of the fermented whey dangke powder included yield, water content, solubility, and protein and lactose contents. The results showed that the fermented whey dangke powder had a yield of 33.15-49.20%; water content of 2.30-9.07%; solubility of 94.0-99.0%; protein content of 9,70-13,92%; and lactose content of 7.92-15.58%. Carrageenan level has a very significant effect (P<0.01) on yield, water content, and lactose content, and it also has a significant effect (P<0.05) on protein content, while drying time has a significant effect (P<0.05) on lactose content. The use of carrageenan at 8% level and 24-hour drying time is the most optimal treatment to produce the best physicochemical characteristics of fermented whey dangke powder.